THE HYPOGLYCEMIC AND ANTIOXIDATIVE EFFECTS OF CENTELLA ASIATICA AGAINST STZ-INDUCED DIABETIC DISORDERS IN RATS - NEMA A. MOHAMED,; HEBA M. ABDOU, (International Journal of Pharma and Bio Sciences, 2015)
The effect of Centella asiatica on diabetes markers, glucose metabolizing enzymes and pancreas antioxidants was investigated. C. asiatica showed a significant antidiabetic activity by reducing the elevated glucose and glycosylated hemoglobin ratio. The insulin, insulin index, C-peptide levels, the liver and muscle glycogen and body weights were improved in the treated diabetic rats. C. asiatica could normalize the activities of the glucose metabolizing enzymes and improved the decrease in the red and white blood cells, hemoglobin, haematocrit and platelets. The pancreatic antioxidants were also increased by C. Asiatica treatment, while, malondialdehyde was decreased. The results showed that diabetes produced a significant decrease in DNA, RNA and RNA/DNA ratio that was normalized after C. asiatica. The histopathological studies showed regeneration of the pancreatic cells after treatment of the diabetic rats with C. asiatica. In conclusion, C. asiatica might be useful for diabetes management and could be able to antagonize diabetic disorders.